PENGARUH VARIASI DEBIT UDARA MASUK TERHADAP KAPASITAS AIR YANG DIHASILKAN OLEH ATMOSPHERIC WATER GENERATOR - Safi'i, Imam; Aryadi, Widya (Sainteknol : Jurnal Sains dan Teknologi, 2018)
The water extracter from the air is still using the principle of external flow so it is considered cooling efficiency is still not good. In this research using internal air flow by using copper pipe with 2 type of design that is design A and B. This process of heat absorption does not occur suddenly, it takes time to arrive at equilibrium point, therefore the air discharge has affect the cooling process. The results showed that the air discharge affect the capacity of condensate water. Design A produces a maximum water capacity of 145 ml in one hour at 25 lpm, while design B generates maximum condensate water of 178 ml in one hour at 15 lpm.